Design and Development of Strategic Intervention Material for Least Learned Topics in Calculus I - Hernane, Cherry Rose; Agsoy, Ara Juzelle; Bingcula, Daniel; Evardo Jr., Orville J. (Papanda Publisher, 2025)
Calculus is a foundational discipline critical for both academic and professional growth. This study, conducted at a state college in Davao de Oro, Philippines, sought to develop Strategic Intervention Materials (SIMs) to address key challenges in Calculus I. Utilizing a developmental research design, the study followed a modified ADD model comprising three stages: analysis, design, and development. Participants included 44 prospective mathematics teachers, selected through random sampling, and five experts in mathematics education and instructional material development. Data collection involved a survey to identify the least mastered topics and validation sheets. The study identified specific areas of difficulty, including Maxima and Minima, Derivatives of Logarithmic and Exponential Functions, Functions with Arguments Approaching Infinity, Derivatives of Inverse Trigonometric Functions, Antiderivatives of Algebraic Functions, and the Constant of Integration. The resulting SIMs were evaluated and demonstrated outstanding content validity, face validity, clarity of presentation, logical organization, accuracy, and relevance. Calculus instructors are encouraged to integrate these SIMs into their curriculum to enhance student understanding in these challenging areas. The study further recommends that calculus teachers employ varied, research-based methodologies to effectively bridge learning gaps in calculus, ultimately fostering a more comprehensive grasp of fundamental calculus concepts.